The problem as point of departure: The Pyrrhonian aporia, the Derridean perhaps and keeping Philosophical Counselling in the realm of philosophy - Louw, Jaco (The Stellenbosch Socratic Journal, 2021)
Philosophical counselling is generally understood as a movement in practical philosophy that helps counselees, i.e. clients, resolve everyday problems with the help of philosophy. Moving outside of the scope of what philosophy can do, however, is a problem. More specifically, when the philosophical counsellor moves outside of the so-called realm of philosophy into the realm of psychotherapy, i.e. medical framework, problem resolution and ameliorative goals might be on the table. This plays into the hands of critics who state that philosophical counselling is encroaching on the terrain of the mental health professions without, inter alia, the proper evidence of its treatment efficacy. This paper is an attempt to keep the philosophical counsellor in the realm of philosophy, and by doing this to keep them busy with philosophising as such, i.e. philosophising as an end in itself. In particular, the article focuses on a novel interpretation of how to approach the counselee’s problem so that the philosophical counsellor does not fall prey to problem resolving and ameliorative endeavours. To substantiate this novel reinterpretation to the counselee’s problem, I turn to the notions of the Pyrrhonian aporia and the Derridean perhaps, in conjunction with a crucial position exclusively available to the counselee in philosophical counselling.